(untitled) (Global Journal of Management and Business Research, 2015)
This article is useful to small and medium enterprises (SMEs) managers in their decisions on the adoption of accounting information system (AIS) that should fit the environmental uncertainty of SMEs, which will help them to attain competitive advantages as well as better performance. The article examines the impact of environmental uncertainty as moderating on the relationship between AIS and performance SMEs Iraq. The empirical studies investigating a direct relationship between AIS and performance SMEs have attracted criticisms, including the use of a bivariate methodology.